Your guide to pre-schools in Metro Manila - De Ocampo, Maricar Gustilo (Anvil Pub., 2001)
It provides reports on over 100 pre-schools in Metro Manila. It has a section on special children which contains discussions of their particular problems and needs, as well as a listing of Metro Manila pre-schools that can help them.